A181 REAL-LIFE EFFICACY OF ELBASVIR/GRAZOPREVIR (EBV/GZV) FOR THE TREATMENT OF CHRONIC HCV GENOTYPE 1 AND 3 INFECTION. (1st March 2018) - Alimohammadi, A; Kiani, G; Raycraft, T; Shahi, R; Singh, A; Conway, B
Abstract: Background: The introduction of all-oral direct acting antiviral (DAA) regimens has allowed for better tolerated, shorter, and more effective courses of therapy for HCV infection. Elbasvir (EBV, NS5A inhibitor) and grazoprevir (GZV, NS3/4A protease inhibitor) is a new fixed dose combination that has demonstrated sustained virologic response (SVR) rates above 90% in a broad range of treatment-naïve and experienced populations, including people who inject drugs (PWID). Aims: We sought to evaluate the efficacy of EBV/GZV in a clinical setting serving HCV-infected PWID. Methods: An observational evaluation was conducted among HCV-infected patients seen at the Vancouver Infectious Diseases Centre (VIDC), where they had access to a multidisciplinary model of care to address medical, psychiatric, social and addiction-related needs prior to, during and after HCV therapy. All individuals that received EBV/GZV did so according to current clinical guidelines. At the time of the current analysis, the primary endpoint was defined as SVR-4, an undetectable HCV RNA four weeks post-treatment. Demographic and clinical correlates of success were also evaluated. Results: To date, 13 individuals have received EBV/GZV in our program, 7 genotype 1a, 2 genotype 1b, and 4 genotype 3a (EBV/GZV administered in combination with sofosbuvir). Key demographic information includes: mean age 49.5 years, 23% female, 15% cirrhotic, 15% HIV co-infect and 85% current PWID. Adherence rates are high, with all patients having missed 0–2 doses. To date, six patients have reached the primary endpoint and 100% have achieved SVR-4, including 4/4 individuals with genotype 3a infection. Data will be presented on 20 patients with the SVR12 endpoint having been achieved. Conclusions: The combination of EBV/GZV (with or without sofosbuvir) appears highly effective in clinical practice in a population similar to that enrolled in the C-EDGE CO-STAR protocol. If these preliminary data are confirmed, EBV/GZV will become another highly potent therapeutic option available for the treatment of HCV infection in diverse populations, including PWID Funding Agencies: None